Future environmental impacts and vulnerabilities - Fischlin, A.; Ayres, M.; Karnosky, D.; Kellomäki, S; Louman, Bastian; Ong, C; Plattner, G.K.; Santoso, H.; Thompson, I; Booth, T.H.; Marcar, N.; Scholes, B.; et al. (IUFRO, 2009)
The focus of this chapter is on climate-change impacts on the environment, the structure and functioning of forests, on their biodiversity, and on the services and goods provided by forests in order to identify key vulnerabilities. Based on the findings of the IPCC Fourth Assessment Report (IPCC 2007d), we first introduce four clusters (unavoidable, stable, growth, and fast growth) of climate change scenarios commonly sed to quantitatively assess climate change impacts (sub-chapter 3.2). At the global scale (sub-chapter 3.3) as well as in the four domains (boreal – sub-chapter 3.4; temperate – 3.5; subtropical – 3.6; tropical – 3.7), our CCIAV-assessment (see glossary) for forests shows that many forests can adapt to a moderate climate change if water is sufficiently available, notably in currently temperature limited areas (unavoidable, lower end stable). In some temperate or boreal regions, certain forests can even increase their primary productivity in a moderate climate change. However, some of these benefits are easily offset as climate warms and the adaptive capacity of currently water limited, fire or insect prone forests is frequently exceeded already by a limited climate change (unavoidable, stable). Many other forests become also vulnerable to an unmitigated climate change (growth, fast growth) as their adaptive capacity is exceeded. Forests currently sequester significant amounts of carbon; a key vulnerability consists in the loss of this service, and forests may even turn into a net source. Among land ecosystems, forests currently house the largest fraction of biodiversity; unmitigated climate change threatens to put significant parts of it at risk. The boreal domain, being especially sensitive, serves as a model case and is treated in particular depth. Finally, conclusions are drawn to summarize all findings on the global as well as regional scales